Ancient Jewish magic : a history - Bohak, Gideon, 1961- (Cambridge, UK ; New York : Cambridge University Press, 2008)
Gideon Bohak gives an account of the broad history of ancient Jewish magic, from the Second Temple to the rabbinic period. It is based both on ancient magicians' own compositions and products in Aramaic, Hebrew and Greek, and on the descriptions and prescriptions of non-magicians. The main focus is on the cultural make-up of ancient Jewish magic, and special attention is paid to the processes of cross-cultural contacts and borrowings between Jews and non-Jews, as well as to inner-Jewish creativity. Other major issues explored include the place of magic within Jewish society, contemporary Jewish attitudes to magic, and the identity of its practitioners. --From publisher's description.
Jewish magic : a contradiction in terms? -- Jewish magic in the Second Temple period -- Jewish magic in late antiquity : the "insider" evidence -- Non-Jewish elements in late-antique Jewish magic -- How "Jewish" was ancient Jewish magic? -- Magic and magicians in rabbinic literature.
Includes bibliographical references (pages 435-479) and index.
Print version record.
Keywords: Jewish magic -- History; Magic in rabbinical literature; Jewish magic; Magic in rabbinical literature; Magi -- religiösa aspekter -- judendom -- historia; BODY, MIND & SPIRIT / Parapsychology / General; History; Electronic books